Self-insertion as discursive and core-identity of Gibran's Al Mustafa - Al-Khazraji, Nidaa Hussain Fahmi (Linguistics and Culture Review, 2022)
This paper studies the core identity of Al Mustafa (the chosen) in Gibran's book The Prophet (1923) as an individual property by investigating its discursive features as revealed in the words and deeds of the participants in the discourse. The study deals with how Gibran refers to the protagonist and how this portrayal reflects on the identity of the writer. It examines how the prophet refers to himself, his worries and needs, how the interlocutors address him in the discourse, and finally how the telling of the ongoing actions leads to the perception of Al-Mustafa as a prophetic figure. The results show that the source of the power of such a discursive identity is neither nature, nor certain established institutions, but the people of Orphalese themselves (the participants in the discourse), plus those readers of Gibran's book who discern a prophetic figure in his words. The process through which these power works is that of “recognition”, in that rational individuals recognize Al-Mustafa as a Prophet in the discourse. Such recognition is realized as an active “self-achievement” arising as a deserved property of how the prophet's words and deeds are recognized by his followers.